Leaf anatomy of Acanthaceae species: Clinacanthus nutans (Burm.f.) Lindau (Belalai gajah) - Che Amri, Che Nurul Aini; Shahari, Rozilawati; Z, Siti Maisarah; Mohd Yunus, Noor Syaheera; Talip, Noraini (Universiti Kebangsaan Malaysia, 2025)
The growing interest in the potential medicinal sources from the Acanthaceae family serves as a promising foundation for pharmacological research. Leaf anatomy plays a crucial role in plant taxonomy, providing essential characteristics that aid in the identification and understanding of relationships among plant species, particularly those with medicinal value. Anatomical studies are also significant in preventing the misidentification of medicinal species, which can lead to incorrect harvesting of raw materials and issues in drug authentication, especially in pharmaceutical production. Therefore, a comprehensive study of the leaf anatomy of selected species, which is Clinacanthus nutans, was conducted to assess the anatomical variations that are useful for species identification. These species were selected due to their medicinal value in traditional remedies such as relieving inflammation and pain. The study employed various methods, including cross-sections using a sliding microtome, and observation under a light microscope. General characteristics were observed such as types of cystolith cells and trichomes. In conclusion, the findings reveal that leaf anatomical characteristics can serve as additional data for identifying incomplete medicinal plant species.